Trinidad and Tobago. Significant achievements 2015 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Trinidad and Tobago during 2015 are identified, with respect to the needs and interests of the country, strengthening issues such as agribusiness, beekeeping, risk management, antimicrobial resistance and production. Finally, support was provided in financial management, in the production of dairy products, honey, cocoa, goats and ruminants.